Targeted Sequencing of Sorted Esophageal Adenocarcinoma Cells Unveils Known and Novel Mutations in the Separated Subpopulations. Issue 9 (21st September 2020) - Isidori, Federica; Bozzarelli, Isotta; Mastracci, Luca; Malvi, Deborah; Lugaresi, Marialuisa; Molinari, Chiara; Söderström, Henna; Räsänen, Jari; D'Errico, Antonia; Fiocca, Roberto; Seri, Marco; Krishnadath, Kausilia K.; et al.
Abstract : INTRODUCTION: Our study aimed at investigating tumor heterogeneity in esophageal adenocarcinoma (EAC) cells regarding clinical outcomes. METHODS: Thirty-eight surgical EAC cases who underwent gastroesophageal resection with lymph node dissection in 3 university centers were included. Archival material was analyzed via high-throughput cell sorting technology and targeted sequencing of 63 cancer-related genes. Low-pass sequencing and immunohistochemistry (IHC) were used to validate the results. Results: Thirty-five of 38 EACs carried at least one somatic mutation that was absent in the stromal cells; 73.7%, 10.5%, and 10.5% carried mutations in tumor protein 53, cyclin dependent kinase inhibitor 2A, and SMAD family member 4, respectively. In addition, 2 novel mutations were found for hepatocyte nuclear factor-1 alpha in 2 of 38 cases. Tumor protein 53 gene abnormalities were more informative than p53 IHC. Conversely, loss of SMAD4 was more frequently noted with IHC (53%) and was associated with a higher recurrence rate ( P = 0.015). Only through cell sorting we were able to detect the presence of hyperdiploid and pseudodiploid subclones in 7 EACs that exhibited different mutational loads and/or additional copy number amplifications, indicating the high genetic heterogeneity of these cancers. DISCUSSION: Selective cell sorting allowed the characterization of multiple molecular defects in EAC subclones that were missed in a significant number of cases when whole-tumor samples were analyzed. Therefore, this approach can reveal subtle differences in cancer cell subpopulations. Future studies are required to investigate whether these subclones are responsible for treatment response and disease recurrence.